Applying Social Cognitive Theory in Predicting Physical Activity Among Chinese Adolescents: A Cross-Sectional Study With Multigroup Structural Equation Model - Liu, Jianxiu; Zeng, Muchuan; Wang, Dizhi; Zhang, Yao; Shang, Borui; Ma, Xindong (Frontiers in Psychology, 2022)
This cross-sectional study aimed to assess the social cognitive determinants’ applicability among Chinese adolescents and examine whether the predictability of the social cognitive theory (SCT) model on physical activity (PA) differs across gender (boys and girls) and urbanization (urban and suburban). A total of 3000 Chinese adolescents ranging between the ages of 12-15 were randomly selected to complete a set of questionnaires. Structural equation modeling (SEM) was performed to investigate the relationships between social cognitive variables and PA in urbanization and gender subgroups. The overall model explained 38.9% of the variance in PA. Fit indices indicated that the structural model of SCT was good: RMSEA = 0.047, RMR = 0.028, GFI = 0.974, AGFI =0.960, TLI = 0.971, CFI = 0.978. Regarding the subgroup analysis, Social support (CR = 2.118; p < 0.001) had a more substantial impact on the PA of adolescents in suburban areas than that in urban areas, whereas self-regulation (CR = -2.896, p < 0.001) had a more substantial impact on PA of adolescents in urban areas than in suburban areas. The results indicate that the SCT model predicts PA of Chinese adolescents substantially. SCT model could apply over a range of subgroups to predict PA behavior, and should be considered comprehensively when designing interventions. These findings would profoundly benefit PA among Chinese adolescents, especially across genders and urbanization.